Tantangan Pendidikan Akhlak pada Sistem Pembelajaran Daring - Iwantoro, Iwantoro; Achmad, Wachyudi (Journal of Islamic Education, 2022)
The existence of the Covid-19 pandemic, which is the main reason why the activities of the world community are diverted, from offline activities to online, cannot be separated from the Indonesian people who also feel the impact, especially the Indonesian education world. Community representatives in the education aspect are required to issue policies related to learning system innovations that can be used to cope with the impact of the Covid-19 pandemic. This study purposed to describe the process of inculcating moral education value to the student's learning during the COVID-19's pandemic (E-learning). Methods for extracting data by using literature study either through the theories from references sourced books or from research results from educational journals. The results of this study suggest that the cultivation of students' moral education is related to the active role of parents. Teachers need to build and carry out a comprehensive approach with the parents. The active role of parents can be in the form of giving a good examples and habits during the pandemic.